Physico-Chemical Characterization and X-Band Dielectric Behaviour of Agricultural Soils from Mantha Taluka, Jalna District, India - L. Shinde, Amit; Deshmukh, Sushant (International Journal of Aquatic Research and Environmental Studies, 2026)
This study investigates the physico-chemical properties and X-band dielectric behaviour of agricultural soils collected from Mantha Taluka, Jalna district, Maharashtra, India. Thirty surface soil samples obtained from four representative villages were analyzed for physical properties, including texture and moisture content, and chemical properties such as pH, electrical conductivity, organic carbon, macronutrients, secondary nutrients, and micronutrients. X-band dielectric measurements were performed at a fixed frequency of 9.685 GHz using a microwave waveguide technique to determine dielectric constant, dielectric loss, loss tangent, electrical conductivity, and penetration depth. The results reveal notable village-wise variation in soil texture, moisture status, and chemical fertility parameters. Dielectric properties exhibited strong sensitivity to soil moisture content and texture, with higher dielectric constant observed in moisture-rich and finer-textured soils. Correlation analysis confirmed that soil moisture and clay fraction are the dominant factors controlling X-band dielectric response. The findings demonstrate the potential of X-band dielectric measurements for agricultural soil assessment and microwave-based soil moisture monitoring in semi-arid regions.
Keywords: Agricultural soils; X-band dielectric properties; soil moisture; soil texture